Latin America's economic development : confronting crisis - Dietz, James L., 1947- (Boulder : L. Rienner Publishers, 1995)
"Twenty articles on a wide range of major economic issues facing the region. Includes sections on economic history, inflation, balance of payments, transnational corporations, development strategies (e.g., import substitution, export-led growth), income distribution, labor markets, and the role of women. Excellent for classroom use"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references and index
Keywords: Latin America -- Economic conditions -- 1982-; Latin America -- Economic policy